Entre o legislador e o intérprete: o binômio método-mérito na ADPF 132/ADI 4277 do conflito institucional entre poder legislativo e poder judiciário - Paulino Filho, Ronaldo José de Sousa (2014)
This research''s goal is to study the relationship between the legislator and the interpreter, relating this conflict of roles in these institutions to the figure of minority groups, using the decision of ADPF 132/ADI 4277 as an example of this confrontation. This is a recent phenomenon in brazilian reality, accompanied by a strong growth performance of the activist judiciary, and its widely discussed role. This attitude reaches consequences of different levels, and encompasses a variety of precepts from the structure of powers, institutional harmony, functional performance and social impact. Guided by an increasingly complex and pluralistic society, minority figures appear as vulnerable. The phenomenon of a disharmonious relationship between the institutions that hold power, more explicitly between the Legislature and the Judiciary, is based on this social and political context today. The method and the substance of the conflict resolution consist in a kind of analogy related to confrontation and interference to the prerogatives attributed mainly to parliamentarians and conflict resolution by the judiciary, highlighting the effective decision related to the merits, but illegitimate for this institution. In other words, questioning the need - over judicialization. This is a fundamental debate and has its great importance for the development of the democratic state with rule of law; the social reality and its relation to democracy. It leads to the understanding that this is a phenomenon that if not established with the required care and attention, may cause severe side effects and severe risks to the respect of the democratic ideal. This situation reveals the vulnerability and instability of society, especially the minorities in relation to the controversy of the judicial activism. A bibliographic research is used, qualitative with deductive method, seeking to understand the causes and consequences of the relation of minority groups, exemplified by the decision of the Supreme Court in ADPF132/ADI 4277, linked to the conflict between the legislator and the interpreter.